The Effectiveness of Circumlocution Strategy towards the Students’ Speaking Skills at SMA-IT Al-Biruni Makassar - Wardana, Nur Fadhilah; Ilmiah; Burhanuddin, Wildan (Journal of Language Testing and Assessment, 2023)
This research’s aim is to find out whether the circumlocution strategy effectively improves the students’ speaking skills at SMA-IT Al-Biruni Makassar. This research used a pre-experimental method which consisted the eleventh-grade students of SMA-IT Al-Biruni Makassar as the subjects. The research instruments for data collection used in this research are the pre-test and post-test to determine students' skills in terms of fluency before and after treatment. The result of this research showed that the t-test value was higher than t-table value. The mean score of the post-test is higher than the mean score of the pre-test. It means that the null hypothesis (H0) was rejected while the alternative hypothesis (H1) was accepted. In other words, there is significant difference between the result of the pre-test and post-test in teaching speaking skill in fluency by using circumlocution strategy. Based on the findings, the researcher concluded that the circumlocution strategy effectively improved students' speaking skills in terms of fluency in the eleventh grade at SMA-IT Al-Biruni Makassar.